Preparation method of hydrophobic TiO2 with function of efficient photocatalytic conversion of plastic in neutral aqueous solution
The preparation of hydrophobic TiO2 by one-step hydrothermal method solves the problem of low conversion efficiency of photocatalytic plastics in neutral aqueous solutions, and realizes high-efficiency photocatalytic polyethylene plastics, which has strong oxygen adsorption and superoxide radical generation capabilities, simplifies the process and reduces the The cost.
Patent Information
- Application Number
- CN202411240298.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-17
AI Technical Summary
The prior art is difficult to efficiently photocatalyze plastic waste in neutral aqueous solutions. The hydrophilic surface of traditional photocatalysts makes it difficult to generate superoxide radicals, resulting in low photocatalytic efficiency and high chemical pretreatment costs.
Using one-step hydrothermal method, using n-butyl titanate as the precursor, ethylenediaminetetraacetate as the morphological control agent, and oleamine as the hydrophobic layer control agent, TiO2 material with hydrophobic properties was prepared to achieve neutrality High-efficiency photocatalytic plastic conversion in aqueous solution.
The prepared hydrophobic TiO2 material has strong oxygen adsorption capacity and superoxide radical generation ability in neutral aqueous solution, which significantly improves the conversion efficiency of photocatalytic polyethylene plastics, is simple to operate, low cost, and has practical application potential.
Smart Images

Figure HDA0005029040800000011 
Figure HDA0005029040800000012 
Figure HDA0005029040800000021
Abstract
Description
Technical Field
[0001] The invention relates to the field of material preparation and plastic waste conversion, and in particular to a method for preparing hydrophobic TiO2 with the function of highly efficient photocatalytic conversion of plastics in a neutral aqueous solution. Background Art
[0002] Since its invention, plastic has played an irreplaceable role in human society due to its versatility and low manufacturing cost. However, the scrap management of non-degradable plastic products is a global challenge that cannot be ignored. As of 2024, the cumulative amount of waste plastics in the world has reached 6.4 billion tons, causing irreversible damage to the ecosystem. Photocatalytic plastic conversion technology can use solar energy to transform plastic waste into high-value-added chemicals (such as ethylene, ethanol, etc.), providing a new opportunity for the upgrading and recycling of plastic waste.
[0003] In traditional photocatalytic plastic systems, photocatalysts such as titanium dioxide (TiO2) generate photogenerated electrons and holes under solar irradiation. Photogenerated holes can catalyze plastic waste by generating hydroxyl radicals (·OH). This determines that good dispersion and adsorption of plastic waste in water are necessary conditions for the reaction to occur. Therefore, chemical pretreatment to solubilize plastic waste and promote the contact between plastic waste and photocatalysts is a necessary condition for conventional photocatalytic plastic systems to achieve reasonable efficiency. However, acid-base chemical pretreatment methods are economically unfeasible. In the latest study of simulated photocatalytic pilot plants by Reisner et al., it was found that the treatment of highly corrosive acid-base solutions accounted for more than 85% of the operating costs (Nat Sustain 4, 383–391 (2021). https: / / doi.org / 10.1038 / s41893-020-00650-x). Therefore, in order to meet the requirements of sustainable development and low cost, it is urgent to develop new materials that can effectively photocatalyze the conversion of plastics in neutral aqueous solutions.
[0004] Superoxide radical (·O2-) is a powerful oxidizing species that can break CC bonds in plastics through β-shearing. More importantly, superoxide radical (·O2-) has an ultra-long transfer lifetime of 1ms, which is about 10 times longer than that of hydroxyl radical (·OH). 5 times, which makes it have a long transfer distance and can become an ideal intermediate for energy transfer between photocatalysts and plastic waste, helping to get rid of chemical pretreatment. However, since traditional photocatalysts mostly have hydrophilic surfaces, it is difficult for O2 to be adsorbed, and the diffusion coefficient of O2 in water is low (1.98×10 -9 m 2 / s), which results in too low O2 concentration on the photocatalyst surface. -Therefore, constructing TiO2 materials with hydrophobic properties is conducive to the production of ·O2-, which can greatly improve the photocatalytic plastic conversion performance in neutral aqueous solution, and has important scientific research and practical application value.
[0005] To date, there is no literature or published patent for the synthesis of hydrophobic TiO2 that can efficiently photocatalyze plastics in neutral aqueous solution. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing hydrophobic TiO2 with the function of efficient photocatalytic conversion of plastics in a neutral aqueous solution. The method adopts a one-step hydrothermal method, uses n-butyl titanate as a precursor, ethylenediaminetetraacetate as a morphology control agent, and oleylamine as a hydrophobic layer control agent to prepare TiO2 with hydrophobic characteristics. The process is simple and the cost is low. The problem that existing materials are difficult to achieve efficient photocatalytic conversion of plastics in a neutral aqueous solution can be solved. The method has the potential for large-scale application and extremely strong practical application value.
[0007] The technical solution of the present invention is:
[0008] A method for preparing hydrophobic TiO2 with a function of efficient photocatalytic conversion of plastics in a neutral aqueous solution, using n-butyl titanate as a precursor, ethylenediaminetetraacetate as a morphology control agent, and oleylamine as a hydrophobic layer control agent. The precursor, the morphology control agent, and the hydrophobic layer control agent are first placed in a hydrothermal reactor for hydrothermal growth, and finally the hydrophobic TiO2 material with a function of efficient photocatalytic conversion of plastics in a neutral aqueous solution is obtained through cooling, washing, and drying.
[0009] The method for preparing the hydrophobic TiO2 obtains a hydrophobic TiO2 material with a thickness of 1.2 to 1.6 nm, has hydrophobic properties, and a water contact angle of more than 100°.
[0010] The method for preparing the hydrophobic TiO2 can obtain a hydrophobic TiO2 material having strong oxygen adsorption capacity and superoxide free radical generation capacity under light conditions.
[0011] The preparation method of hydrophobic TiO2 has the following performance indicators: under neutral aqueous solution conditions, the photocatalytic polyethylene plastic yield is greater than 20 μmol g -1 h -1 After 6 hours of photocatalytic reaction, the size of polyethylene plastic particles decreased from more than 500μm to 130μm~270μm.
[0012] In the preparation method of hydrophobic TiO2, the neutral aqueous solution is deionized water with a pH of 7.
[0013] In the method for preparing hydrophobic TiO2, the volume ratio of oleylamine to n-butyl titanate precursor is in the range of 4 to 6, and the mass ratio of ethylenediaminetetraacetate to n-butyl titanate precursor is in the range of 0.02 to 0.1.
[0014] The hydrophobic TiO2 preparation method has the following hydrothermal growth conditions: temperature 140°C to 220°C, reaction time 2h to 48h.
[0015] The preparation method of the hydrophobic TiO2 comprises the following steps: hydrothermal growth, after cooling to room temperature, first filtering or centrifuging the solution and precipitate obtained after the reaction, and then washing, drying and collecting.
[0016] The design ideas of the present invention are as follows:
[0017] In the traditional photocatalytic conversion of plastics system, photocatalysts such as TiO2 generate electrons and holes under solar irradiation. Photogenerated holes can catalytically convert plastic waste by generating hydroxyl radicals (·OH). This determines that good dispersion and adsorption of plastic waste in water are necessary conditions for the reaction to occur. Therefore, chemical pretreatment to solubilize plastic waste and promote the contact between plastic waste and photocatalyst is a necessary condition for the conventional photocatalytic conversion of plastics system to achieve reasonable efficiency. Superoxide radicals·O2 - It has an ultra-long transfer lifetime of 1 ms, which is about 10 times longer than OH (10 ns). 5 times, which makes it have a long transfer distance and can become an ideal intermediate for energy transfer between photocatalysts and plastic waste, helping to get rid of chemical pretreatment. However, most traditional photocatalysts have hydrophilic surfaces, making it difficult for O2 to be adsorbed, resulting in superoxide radicals·O2 - Therefore, constructing TiO2 materials with hydrophobic properties helps - The production of can achieve a significant improvement in the photocatalytic plastic conversion performance in neutral aqueous solution.
[0018] The advantages and beneficial effects of the present invention are:
[0019] 1. The hydrophobic TiO2 synthesized by the method of the present invention has the function of efficient photocatalytic conversion of plastics in neutral aqueous solution, and has great practical application potential in the field of plastic upgrading and recycling.
[0020] 2. The present invention utilizes n-butyl titanate precursor, ethylenediaminetetraacetate morphology control agent, and oleylamine hydrophobic layer control agent to realize the preparation of hydrophobic TiO2, and the operation is simple and fast, and has broad application prospects in the field of material synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 : The morphology and crystal structure of hydrophobic TiO2 samples. Figure 1 (a) is a transmission electron microscope (TEM) test photograph, and the scale bar in the figure is 200nm. Figure 1 (b) is an atomic force microscope (AFM) test photograph, with a scale of 1 μm. Figure 1 (c) Figure 1 (a) Height distribution curve of the selected blue area, where the horizontal axis Distance represents the distance range (nm) and the vertical axis Height represents the thickness (nm). Figure 1 (d) is the X-ray diffraction pattern of hydrophobic TiO2, where the abscissa represents the diffraction angle 2θ (degree) and the ordinate Intensity represents the intensity (au).
[0022] Figure 2 : Comparison of hydrophobicity of hydrophobic TiO2 samples and traditional non-hydrophobic TiO2 samples. Figure 2 (a) is the water contact angle test result of traditional non-hydrophobic TiO2. Figure 2 (b) is the water contact angle test result of hydrophobic TiO2.
[0023] Figure 3 :Comparison of oxygen adsorption capacity between hydrophobic TiO2 samples and traditional non-hydrophobic TiO2 samples, as well as the generation capacity of superoxide radicals (·O2-). Figure 3 (a) is the test result of oxygen temperature programmed desorption, where the horizontal axis Temperature represents temperature (℃), and the vertical axis TCD signal represents signal intensity (au). Figure 3 (b) is the electron spin resonance spectrum of superoxide free radical (·O2-), where the horizontal axis Magnetic field represents the magnetic field intensity (mT) and the vertical axis Intensity represents the signal intensity (au).
[0024] Figure 4 : Plastic conversion performance of hydrophobic TiO2 samples in neutral aqueous solution. Figure 4 (a) is the particle size of the plastic before reaction and the corresponding photo. The horizontal axis PE size represents the polyethylene plastic particle size (μm), the vertical axis Proportion represents the percentage (%), and the inset is the corresponding optical photo. Figure 4 (b) shows the size of plastic particles after 6 hours of photocatalysis and the corresponding photo. The horizontal axis PE size represents the size of polyethylene plastic particles (μm), the vertical axis Proportion represents the percentage (%), and the inset is the corresponding optical photo. Figure 4 (c) The horizontal axis represents the sample type, and the vertical axis Yield represents the yield (μmol g -1 h -1 ). DETAILED DESCRIPTION
[0025] In the specific implementation process, the present invention proposes a method for preparing hydrophobic TiO2 with the function of efficient photocatalytic conversion of plastics in neutral aqueous solution, using n-butyl titanate as a precursor, ethylenediaminetetraacetate as a morphology control agent, and oleylamine as a hydrophobic layer control agent. First, the precursor and the control agent are placed in a hydrothermal reactor for hydrothermal growth, and finally the hydrophobic TiO2 material is obtained after cooling, washing and drying. The specific process of the method is as follows:
[0026] In the polytetrafluoroethylene-lined chamber of the reactor, add 2 ml of n-butyl titanate precursor, 10 ml of oleylamine and 0.2 g of disodium ethylenediaminetetraacetate. After stirring for 0.5 h until fully dissolved, the reactor consisting of the polytetrafluoroethylene liner sealed in a stainless steel jacket is placed in an oven and hydroheated to 200 ° C for 24 h. After cooling to room temperature, the solution and precipitate obtained after the reaction are first filtered or centrifuged to obtain a sample, and then the sample is washed three times in ethanol and deionized water respectively, and dried and collected in an oven at 60 ° C to obtain a hydrophobic TiO2 material with efficient photocatalytic conversion of plastics in a neutral aqueous solution.
[0027] The present invention is further described in detail below through examples and drawings.
[0028] Example 1
[0029] The morphology and crystal structure of hydrophobic TiO2 samples were studied.
[0030] Morphological characterization equipment: transmission electron microscope (JEM-2100F), atomic force microscope YPHER HV. Structural characterization equipment: X-ray diffractometer Rigaku D / max 2500, CuKa ray. Figure 1 As shown in (a), the hydrophobic TiO2 is in the form of ultra-thin nanosheets. Figure 1 (b) and Figure 1 As shown in (c), the thickness of the hydrophobic TiO2 is about 1.4 nm. Figure 1 (d) shows the X-ray diffraction pattern of hydrophobic TiO2. As can be seen from the figure, the structure of hydrophobic TiO2 is anatase titanium dioxide crystal phase.
[0031] Example 2
[0032] The hydrophobicity of hydrophobic TiO2 was studied by comparing the hydrophobic TiO2 samples with the traditional non-hydrophobic TiO2 samples.
[0033] Hydrophobic characterization equipment: Contact angle tester JC2000A. Figure 2 (a) It can be seen that the water contact angle of traditional non-hydrophobic TiO2 is 0°, indicating that traditional non-hydrophobic TiO2 is hydrophilic. Figure 2(b) It can be seen that the water contact angle of hydrophobic TiO2 is 125°, indicating that hydrophobic two-dimensional titanium dioxide has strong hydrophobic properties.
[0034] Example 3
[0035] The hydrophobic TiO2 sample and the traditional non-hydrophobic TiO2 titanium dioxide sample were used as comparison objects to compare the oxygen adsorption capacity and superoxide radical (·O2-) generation capacity of hydrophobic TiO2.
[0036] Oxygen adsorption capacity characterization equipment: Oxygen programmed temperature desorption instrument (Micromeritics / Autochem 2920). Superoxide free radical (·O2-) generation capacity characterization equipment: Electron spin resonance instrument (JEOLJES-FA200). Figure 3 (a) It can be seen that hydrophobic TiO2 has a stronger oxygen adsorption capacity, and its oxygen desorption temperature (180.4℃) is significantly higher than that of non-hydrophobic TiO2 (82.3℃). Figure 3 (b) It can be seen that hydrophobic TiO2 has a stronger ability to produce superoxide radicals, and the superoxide radical signal intensity is significantly higher than that of non-hydrophobic TiO2.
[0037] Example 4
[0038] The photocatalytic plastic conversion performance of hydrophobic TiO2 samples in neutral aqueous solution was studied.
[0039] Photocatalytic plastic test conditions: The photocatalytic reaction light source is a xenon lamp light source (illuminance: 100mW / cm 2 ). A mixed solution of 100 mg sample, 300 mg polyethylene plastic particles (particle size 500 μm) and 50 ml deionized water was tested for photocatalytic plastic conversion. Multi-channel gas chromatography (GC) was used to analyze the gas products of photocatalytic plastic conversion, such as H2, CH4, CO, etc. Liquid nuclear magnetic resonance and gas chromatography were used to analyze the liquid products of photocatalytic plastic conversion, such as C2H5OH, CH3OH, etc. Figure 4 As shown, photos of the plastic before and after the reaction were taken using an optical microscope. Figure 4 (a) The results show that the size of plastic particles before the reaction is 500μm to 540μm. Figure 4 (b) The results show that the size of the plastic particles is 130μm to 270μm after 6h of reaction. Figure 4 (c) The results show that the plastic conversion performance of hydrophobic TiO2 is 36.1 μmol g -1 h -1 The plastic conversion performance of traditional non-hydrophobic TiO2 is 1.6 μmol g -1 h -1The photocatalytic plastic conversion performance of hydrophobic TiO2 is nearly 22 times higher than that of traditional non-hydrophobic TiO2.
[0040] The results of the examples show that the preparation method of the hydrophobic TiO2 provided by the present invention can effectively prepare hydrophobic TiO2. Compared with the traditional non-hydrophobic TiO2, the hydrophobic TiO2 has strong oxygen adsorption capacity and superoxide radical generation capacity. Compared with the traditional non-hydrophobic TiO2, the obtained TiO2 has high-efficiency photocatalytic plastic conversion performance in neutral aqueous solution. This method synthesizes a hydrophobic TiO2 material with high-efficiency photocatalytic plastic function in neutral aqueous solution for the first time, and is simple to operate, low cost, and has extremely strong practical application value and large-scale application potential.
Claims
1. A method for preparing hydrophobic TiO2 with high efficiency photocatalytic conversion of plastics in neutral aqueous solution, characterized in that: Using n-butyl titanate as a precursor, ethylenediaminetetraacetate as a morphology control agent, and oleylamine as a hydrophobic layer control agent, the precursor, morphology control agent, and hydrophobic layer control agent are first placed in a hydrothermal reactor for hydrothermal growth, and finally, after cooling, cleaning, and drying, a hydrophobic TiO2 material with efficient photocatalytic conversion of plastics in a neutral aqueous solution is obtained.
2. The method for preparing hydrophobic TiO2 according to claim 1, characterized in that: The hydrophobic TiO2 material obtained by the method has a thickness of 1.2 to 1.6 nm, has hydrophobic properties, and a water contact angle of more than 100°.
3. The method for preparing hydrophobic TiO2 according to claim 1, characterized in that: The hydrophobic TiO2 material obtained by the method has strong oxygen adsorption capacity and superoxide free radical generation capacity under light conditions.
4. The method for preparing hydrophobic TiO2 according to claim 1, characterized in that: The performance indicators of the hydrophobic TiO2 material obtained by this method are as follows: Under neutral aqueous solution conditions, the photocatalytic polyethylene plastic yield is > 20 μmol g -1 h -1 After 6 hours of photocatalytic reaction, the size of polyethylene plastic particles decreased from more than 500μm to 130μm~270μm.
5. The method for preparing hydrophobic TiO2 according to claim 1 or 4, characterized in that: The neutral aqueous solution is deionized water with a pH of 7.
6. The method for preparing hydrophobic TiO2 according to claim 1, characterized in that: The volume ratio of oleylamine to n-butyl titanate precursor is in the range of 4 to 6, and the mass ratio of ethylenediaminetetraacetate to n-butyl titanate precursor is in the range of 0.02 to 0.
1.
7. The method for preparing hydrophobic TiO2 according to claim 1 or 6, characterized in that: The conditions for hydrothermal growth are: temperature 140°C ~ 220°C, reaction time 2h ~ 48h.
8. The method for preparing hydrophobic TiO2 according to claim 1, characterized in that: After the hydrothermal growth is cooled to room temperature, the solution and precipitate obtained after the reaction are first filtered or centrifuged, and then washed, dried and collected.